(3JgPjH GdceGd aj CSeGA GdQLGds - (3jhSa Hf YHO GdQMef Hf jhSa, CHh GdMLGL, LeGd GdOjf GHf GdRcj CHj eMeO GdbVGYj GdcdHj GdeRj,J (B742 (3g` s; (3GdLeGYjdj , Jbj GdOjf CHh eMeO,J (B600 (3g` s
(3ChdgG (B:s
(3GdMeO ddg GdPi CfGQ WQjb GdMb EdN s
(3BNQgG (B:s
(3jfJgi YfO GSe KhQ s
(3Vef eLehY , JQJjHgG (B: (3GdChds
(3GdfSNI HgG MhGTs
(3Ydjg ELGRGJ ef GdeDdas
(3fSNI NGeSIs
(3bQf GdfSN (B:s
(3GdbQf GdKGefs
(3JHUQI GdYfhGf (B:s
Keywords: (3GdJGQjNs